The relationship between senior management team (SMT) and teachers’ attitude towards achieving high performing school (HPS) status: a case study of primary schools at Johor Bahru / Farhana Yaakub ...[et al.] - Yaakub, Farhana; Boerhannoeddin, Ali; Zainuddin, Muhammad Yazrin Zaifuddin; Bahrin, Ani Juaini (Faculty of Administrative Science and Policy Studies, 2014)
The government has introduced the concept of High Performing School (HPS) as a new excellent school standard to be achieved by all schools in order to realise a national dream and vision to be a developed country in 2020 and to pursue educational development and improvement. However, the teachers perceived that the initiatives or changes would mean a heavier workload, a hindrance and a cause of confusion towards their profession. In Malaysia, a special committee was established to review the workload of teachers. Besides teaching, teachers had to deal with extra-curricular activities, classroom, student affairs, administration and clerical and other additional works. Therefore, in realizing the country’s aims in education, assessing teachers’ attitude towards these initiatives is paramount for its success. This study focuses on the association between Senior Management Team (SMT) and teachers’ attitude towards achieving HPS status. Sample population used to analyze the association and correlations were primary schools teachers in Johor Bahru, Malaysia. In addition, the data collection was done through distribution of questionnaires. After the data analysis process had been completed, the results surprisingly, indicated that this factor have positively associated with teachers’ attitude towards achieving HPS status. The result had proved on the importance of this element to influence the development of positive attitude of teachers to support the achievement of these initiatives. It is hoped that the results of the study may be useful to relevant government agencies, school’s leadership and other parties involved directly or indirectly to further assess the needs and support that should be given to teachers who work hard to meet the nation's aspirations to improve the quality of national education.